Extension and validation of SIMMER III code for gas cooled fast reactor. (July 2015) - Chen, X.-N.; Andriolo, L.; Rineiski, A.; Bubelis, E.; Mayer, G.; Bentivoglio, F.
Highlights: SIMMER-III is extended and validated for safety studies of gas cooled fast reactor. Equations of state and thermal physical properties of helium are implemented. ALLEGRO reactor is simulated and the code is validated. Unprotected loss of coolant severe accident is analyzed. Abstract: This paper deals with extension, application and validation of the SIMMER-III code for safety studies of a gas cooled fast reactor. The equations of state and thermal physical properties of the helium gas have been prepared and implemented in the code. The geometric, thermal hydraulic and neutronic models have been set up for the ALLEGRO reactor. The code and the associated model are verified by comparing results of steady state and unprotected loss of flow with 20% remaining flow rate (ULOF-20%) with those obtained by other project partners. Reasonable or good agreements have been achieved for major physical variables. The unprotected loss of coolant accident (ULOCA) is a severe event leading to core melting and degradation that was simulated only by SIMMER in the project. In the initiating phase the clad melts and the fuel sweeps out; this triggers the first power excursion. Then the fuel becomes more mobile and further power excursions take place, which lead to core melting and degradation. The fuel is ejected by the power excursion and then moves relatively slowly to the lower part of the vessel. Finally there are only a few kilograms of fuel escaping from the vessel (into reactor container) and the released thermal energy is about 6 GJ within a period of one minute. The final power stays below 1 MW and the reactor is in a deep sub-criticality state, since half of the fuel is evacuated from the core region.